2011
DOI: 10.1158/1940-6207.capr-10-0377
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Colorectal Cancer Screening Protocol in an Economically and Medically Underserved Population

Abstract: The performance of combining fecal immunochemical tests (FITs) and a high-risk factor questionnaire (HRFQ) in colorectal cancer (CRC) screening in economically and medically underserved populations is uncertain. This study investigated the performance of a CRC screening protocol of combining FITs and an HRFQ as primary screening methods in a rural Chinese population. A CRC mass screening was conducted using FITs and an HRFQ as the first and colonoscopy as the second stage of screening in Jiashan, [2007][2008][… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 23 publications
5
42
1
Order By: Relevance
“…A total of 24,419 study participants signed the written informed consent and participated in this CRC screening program. Basic characteristics of the study participants and positive predictive value of this screening have been reported by Cai et al [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…A total of 24,419 study participants signed the written informed consent and participated in this CRC screening program. Basic characteristics of the study participants and positive predictive value of this screening have been reported by Cai et al [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Following review, 19 studies were eligible for inclusion in the review and meta-analysis (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). A flow chart of the search strategy results is provided in Fig.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…The combined HRFQ has improved compliance rate and screening net sensitivity due to the simultaneous screening design and the overall effectiveness of our screening program. However, the overall false positive rate is high, as is the case in all CRC mass screening programs worldwide [8][9][10][11] . In our CRC mass screening program, 73.3% (false positive rate from iFOBT or HRFQ) of high risk populations previously underwent unnecessary colonoscopy examinations [6,8] .…”
Section: Introductionmentioning
confidence: 99%